Retooling Human Capital to Attain Sustainable Development Goals in Nigeria - Ishola, Babatunde Stephen; Abiodun, Isinkaye Kehinde (LPPM Universitas Jambi, 2025)
The paper focuses on the need to retool human capital development as a strategy to attain sustainable development goals in Nigeria. It identifies changes in technology, increasing personnel demands, and social complexity as factors necessitating the retooling of human capital development in Nigeria. It believes that it can be handled through investment in skill development through education, vocational training, people-centered policy, and management metrics, amongst others. It further observed that human capital development could instigate skills development, career development, succession plans, economic growth, and overall development in Nigeria, if adequate plans and strategies are adopted to critically pursue the human development agenda.